A Balancing Act: Integrating Evidence‐Based Knowledge and Cultural Relevance in a Program of Prevention Parenting Research with Latino/a Immigrants. Issue 2 (26th October 2015) - Parra‐Cardona, José Rubén; López‐Zerón, Gabriela; Domenech Rodríguez, Melanie M.; Escobar‐Chew, A. Rocío; Whitehead, Michael R.; Sullivan, Cris M.; Bernal, Guillermo
Abstract : Family therapists have a unique opportunity to contribute toward the reduction of widespread mental health disparities impacting diverse populations by developing applied lines of research focused on cultural adaptation. For example, although evidence‐based prevention parent training (PT) interventions have been found to be efficacious with various Euro‐American populations, there is a pressing need to understand which specific components of PT interventions are perceived by ethnic minority parents as having the highest impact on their parenting practices. Equally important is to examine the perceived cultural relevance of adapted PT interventions. This qualitative investigation had the primary objective of comparing and contrasting the perceived relevance of two culturally adapted versions of the efficacious parenting intervention known as Parent Management Training, the Oregon Model (PMTO). According to feasibility indicators provided by 112 Latino/a immigrant parents, as well as findings from a qualitative thematic analysis, the core parenting components across both adapted interventions were identified by the majority of research participants as relevant to their parenting practices. Participants exposed to the culturally enhanced intervention, which included culture‐specific sessions, also reported high satisfaction with components exclusively focused on cultural issues that directly impact their parenting practices (e.g., immigration challenges, biculturalism). This investigation illustrates the relevant contributions that family therapy scholars can offer toward addressing mental health disparities, particularly as it refers to developing community‐based prevention interventions that achieve a balance between evidence‐based knowledge and cultural relevance.